Unfolded p53 in Blood as a Predictive Signature Signature of the Transition from Mild Cognitive Impairment to Alzheimer's Disease - Lanni, Cristina; Racchi, Marco; Stanga, Serena; Mazzini, Giuliano; Ranzenigo, Alberto; Polotti, Renzo; Memo, Maurizio; Govoni, Stefano; Uberti, Daniela (Journal of Alzheimer's disease, 2010)
Mild cognitive impairment (MCI) is a syndrome defined as cognitive decline, but not sufficient to meet the criteria for any specific dementia. Although subjects with MCI may have an increased risk to develop AD, this clinical state encompasses several subtypes of cognitive dysfunction of different etiologies, none of which necessarily progresses to AD. The current inability of clinical criteria to accurately identify this at-risk group for AD development is fuelling the interest in biomarkers able to supplement clinical approaches. We recently described a blood-based cytofluorimetric method for conformationally altered p53 protein detection that allows the discrimination of AD patients from control subjects and patients affected by other dementias. The same protein also predicted progression to AD in preclinical patients with MCI two years before clinical diagnosis of AD was made. Herein, we describe these findings and discuss the potential of the test in diagnosing AD.